2004
DOI: 10.1902/jop.2004.75.8.1046
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Diseases and the Risk of Coronary Heart and Cerebrovascular Diseases: A Meta‐Analysis

Abstract: Findings indicated that periodontal infection increases the risk of CHD and CVD. However, this meta-analysis provided no evidence for the existence of strong associations between periodontitis and CHD and CVD. Larger and better-controlled studies involving socially homogeneous populations and measuring specific periodontal pathogens are required to identify a definite association between periodontal disease and the risk of coronary heart disease and cerebrovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
152
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(166 citation statements)
references
References 42 publications
3
152
0
6
Order By: Relevance
“…9,10,12,14 An understanding of this connection is vital for the proper diagnosis, treatment and maintenance of both periodontal and systemic diseases. Clinical observations give the impression that medical doctors are less interested in the relationship between PD and SH when compared with periodontists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10,12,14 An understanding of this connection is vital for the proper diagnosis, treatment and maintenance of both periodontal and systemic diseases. Clinical observations give the impression that medical doctors are less interested in the relationship between PD and SH when compared with periodontists.…”
Section: Discussionmentioning
confidence: 99%
“…If atherosclerotic plaques occur in brain arteries, they can cause stroke; when plaques occur in coronary arteries, they can lead to myocardial infarction. 12,14 Preterm birth and low birth weight are notable health problems associated with PD, and PD related infections may lead to altered cytokine and hormone levels, which may lead to complications during pregnancy. 15,16 The biological mechanisms involved in the relationship between PDs and respiratory diseases remain unclear, but aspiration of bacteria from the oropharynx into the lower respiratory tract may be to blame.…”
Section: Introductionmentioning
confidence: 99%
“…They are highly prevalent, affecting 50 -90% of the worldwide population (19). Mounting evidence has accumulated supporting a role of P. gingivalis infection as a risk factor for several systemic diseases, including preterm birth, heart disease, diabetes, and atherosclerosis (19,(22)(23)(24)(25)(26)(27). These associations indicate a possible role for P. gingivalis infection in the etiology of various systemic diseases.…”
Section: Reactivation Of Latent Hiv-1 Infection By the Periodontopathmentioning
confidence: 99%
“…It has been reported that 10% to 15% of the periodontal patients had been linked to CVD. [17][18][19] We previously showed that periodontopathic pathogens deteriorated ventricular remodeling after MI 20,21) and other cardiovascular diseases. [22][23][24][25][26] However, a detailed mechanism is still to be elucidated.…”
mentioning
confidence: 99%